Study of Economic Reality on Foreign Exchange Accounting - Mukhtar Mukhtar; Seandy Ginanjar (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study tested the gap between foreign exchange accounting treatment and the underlying economic reality, by comparing the regression model between U.S. Companies and Indonesian Companies in one particular economic period. A total sample of 139 companies, consisting of 60 companies with rupiah functional currency domiciled in Indonesia and 79 companies with dollar functional currency domiciled in the United States. The simple regression variable used is comprehensive profit as a dependent variable and foreign exchange gain and loss as an independent variable. Hypothetical conclusions are carried out by testing regression patterns on the underlying economic circumstances. The results of the statsitik regression corssection test showed significant value indicating the influence between variables on a number of companies that have a uniform pattern, conclusions are strengthened by considering the economic situation in the data retrieval situation using criteria such as currency exchange rate, GDP, trade balance and others on each country, while insignificant influence indicates the opposite. Based on the test results and economic analysis shows the results of regression that signfikan in each region with economic conditions that support fluctuations in exchange rate changes in each region. So it is concluded that there is no difference between the treatment of foreign exchange accounting and the underlying economic reality.